Molecular-genetic substantiation of combined therapy in the early postoperative period in diffuse peritonitis - A. P. Vlasov; Sh. S. Al-Kubaisi; T. I. Vlasova; Y. K. Salakhov; N. A. Myshkina; D. A. Romanov; F. A. Ali-Fuad; S. T. Al-Anbari (Вестник хирургии имени И.И. Грекова)
The OBJECTIVE was to give a molecular genetic foundation of combination therapy in the early postoperative period for peritonitis.METHODS AND MATERIALS. 70 patients with diffuse peritonitis were studied: the first (n=35) – patients underwent basic treatment, the second (n=35) – combined treatment with the inclusion of Remaxol and laser irradiation. The severity of endotoxemia and oxidative stress, the state of the hemostasis system and the functional status of the liver were determined. Molecular genotyping of the following genes was performed: beta subunits of platelet fibrinogen receptor (T1565C, ITGB3), fibrinogen (G(-455)A, FGB), catalase (-262C/T, CAT), superoxide dismutase (C47T, SOD2).RESULTS. It was found that the early postoperative period in patients with peritonitis is accompanied by endotoxemia, oxidative stress, impaired functional status of the liver, hypercoagulation and hypofibrinolysis. In patients with conditionally «mutant» genotypes of the studied genes, peritonitis is more severe, the severity of changes in the studied indicators of homeostasis is greater. At the same time, the effectiveness of therapy decreased, the number of complications increased, and the stay of patients in the hospital increased. The early inclusion of Remaxol and laser radiation in basic therapy increases the overall effectiveness of treatment: the severity of endotoxemia and oxidative stress decreases, the functional state of the liver and hemostasis system is restored relatively quickly, and as a result, an improvement in clinical results has been registered (a 37.5 % decrease in the frequency of complications (χ2=3.360, p=0.047) and a reduction in the length of stay of patients in the hospital by 16.6 % (p<0.05)).CONCLUSION. The inclusion of Remaxol and laser therapy in the early postoperative period in the treatment regimen of patients with peritonitis makes it possible to influence pathogenetically important links of the disease relatively quickly, which improves treatment results. This type of therapy is particularly effective in patients with polymorphic genotypes T1565C and C1565C of the ITGB3 gene.